TCAD Simulations and Small Signal Modeling of DMG AlGaN/GaN HFET - Rahis Kumar Yadav; Pankaj Pathak; R M Mehra (International Journal of Electrical and Computer Engineering (IJECE), 2017)
This article presents extraction of small signal model parameters and TCAD simulation of novel asymmetric field plated dual material gate AlGaN/GaN HFET first time. Small signal model is essential for design of LNA and microwave electronic circuit by using the proposed superior performance HFET structure. Superior performances of device are due to its dual material gate structure and field plate that can provide better electric field uniformity, suppression of short channel effects and improvement in carrier transport efficiency. In this article we used direct parameter extraction methodology in which S-parameters of device were measured using pinchoff cold FET biasing. The measured S-parameters are then transformed into Y-parameters to extract capacitive elements and then in to Z-parameters to extract series parasitic elements. Intrinsic parameters are extracted from Y-parameters after de-embedding all parasitic elements of devce. Microwave figure of merits and dc performance are also studied for proposed HFET. The important figure of merits of device reported in the paper include transconductance, drain conductance, current gain, transducer power gain, available power gain, maximum stable gain, maximum frequency of oscillation, cut-off frequency, stability factor and time delay. Reported results are validated with experimental and simulation results for consistency and accuracy.